Development of Electronic Books Using Website 2 APK Builder Pro Based on Science, Technology, Engineering, and Mathematics (STEM) to Improve Learning Outcomes - Chercules; Ismet; Ida Sriyanti (Postgraduate, University of Mataram, 2023)
Development of a science, technology, engineering, and mathematics (STEM)-based climate change electronic book aided by the APK Builder Pro website to improve learning outcomes. This study aims to determine the validity, practicality, and effectiveness of the product to improve learning outcomes. This research aims to produce an Electronic Book Using Website 2 APK Builder Pro based on Science, Technology, Engineering, and Mathematics (STEM). Product development is based on students' needs for 21st century learning with the industrial technology revolution 4.0 which is identical to the utilization of technology, information, and communication. The method used in this research is research and development (R&D) with the ADDIE model development design consisting of five stages, namely analysis, design, development, implementation, and evaluation. The results of this study indicate that the percentage of validity of the Science, Technology, Engineering, and Mathematics (STEM)-based climate change electronic book averaged 86.7% with very valid criteria, the percentage of product practicality averaged a one to one test of 86 2%, a small group test of 83%, and a response from a physics teacher of 91% with very practical criteria, and the N-gain test tested on 32 students obtained an average result of 0.8 with high percentage criteria with very effective criteria. Therefore, it can be concluded that the electronic book of climate change based on Science, Technology, Engineering, and Mathematics (STEM) assisted by the APK Builder Pro website is valid, practical and effective to improve student learning outcomes.